Intimate and Personal Sphere in the System of Vital Values of the Anomalous Person – the Offender - A. M. Bolshakova; T. O. Perevozna; I. O. Videnieiev; O. M. Khartsii (Law and Safety)
The study of the peculiarities of the structural and dynamic characteristics of the value and content sphere of the anomalous personality remains within the scope of actual psychological problems. The purpose of this study is to analyze the peculiarities of value orientations that represent the intimate and personal sphere, in the ideal representation, within conscious and unconscious aspects, as well as to analyze the place of the intimate and personal sphere in the structure of the assessment of reality in persons with specific personality disorders, who committed illegal actions.